2020
DOI: 10.3390/cancers12071864
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Characteristics Obtained Using Computed Tomography as Prognosticators in Patients with Castration-Resistant Prostate Cancer

Abstract: Limited studies have investigated the correlation between body composition and prostate cancer outcomes. We analyzed the effect of muscle mass and quality on castration-resistant prostate cancer (CRPC) outcomes. Skeletal muscle index (SMI) and skeletal muscle attenuation (SMA) were measured for 411 patients at the L3 vertebral level using computed tomography at CRPC diagnosis and were dived to low and high groups at the value of median. Analysis of the skeletal phenotypes and age (<70 and >70 years) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 33 publications
(43 reference statements)
0
24
0
Order By: Relevance
“…Sarcopenia has become a topic of great interest in oncology [68]; however, poorly understood given the lack of reporting on assessment characteristics and definitions. For example, although studies had reported the time of body composition assessment [25,33,34,36,37,[40][41][42][43]45], the high heterogeneity and lack of standardisation could misclassify prostate cancer patients with obesity or sarcopenia and, therefore, mask the impact of these outcomes on overall survival. Future research should better inform definitions (i.e., cut-off values and rationale) and time of assessments, and information about clinical factors associated with muscle mass accrual or maintenance in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sarcopenia has become a topic of great interest in oncology [68]; however, poorly understood given the lack of reporting on assessment characteristics and definitions. For example, although studies had reported the time of body composition assessment [25,33,34,36,37,[40][41][42][43]45], the high heterogeneity and lack of standardisation could misclassify prostate cancer patients with obesity or sarcopenia and, therefore, mask the impact of these outcomes on overall survival. Future research should better inform definitions (i.e., cut-off values and rationale) and time of assessments, and information about clinical factors associated with muscle mass accrual or maintenance in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 and Supplementary eAppendix 2). A total of 16 cohort studies undertaking retrospective analyses [16,24,25,[33][34][35][36][37][38][39][40][41][42][43][44][45] were included in the primary analysis. During the eligibility assessment, six additional studies [46][47][48][49][50][51] were initially selected and authors contacted given the lack of specific information on the results for prostate cancer patients.…”
Section: Studies Included and Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Myosteatosis is an umbrella term used to describe varying adipose compartments within the SM (intermuscular and intramuscular adipose tissue and intramyocellular lipids). Myosteatosis occurs more often in individuals with diabetes [ 45 ], increases with antiandrogen therapy [ 46 ], and is a negative prognostic indicator of OS in MPC [ 23 , 47 ]. Based on the magnitude of the HRs and the visual representation of the curves in Figure 1 , our pilot data signals myosteatosis may be a particularly worrisome condition for Black men.…”
Section: Discussionmentioning
confidence: 99%
“…The most evaluated (69.3%) outcome among the studies was survival, 12,13,[15][16][17][18][19][20][21][34][35][36]41,42,45,46,[50][51][52][53][54]57,58,60,[62][63][64][65][66][67][68][69][70]72,[74][75][76][77][78][79][80]83,84,87,88,91,[93][94][95][96][97][98][100][101]…”
Section: Evaluated Outcomesmentioning
confidence: 99%